(untitled) (Journal of Science Foundation, 2016)
A 22 years female student presented with sudden severe abdominal pain in left upper quadrant followed by abdominal distension. She attended in surgery unit of a tertiary health care center. On examination she was in shock and the abdomen was distended, tender. She was evaluated as surgical acute abdomen and emergency laparotomy revealed rupture of spleen and splenectomy was done. Her CBC showed gross leucocytosis with predominance of neutrophils and significant number of myelocytes and the PBF showed the features of chronic phase of chronic myeloid leukaemia. BCR-ABL was positive from bone marrow that confirms the diagnosis. Splenomegaly is a common presentation of CML. However spontaneous rupture of spleen is a very rare presentation of CML. Journal of Science Foundation, 2015;13(2):52-54 DOI: http://dx.doi.org/10.3329/jsf.v13i2.27935